Use the Product Rule to find the derivative of the function

Calculus
Tutor: None Selected Time limit: 1 Day

f(x) = (x3 − 2x)(4x2 + 2x)

Mar 18th, 2015

f(x) = (x^3 − 2x)(4x^2 + 2x)

    =(x^3-2x)(8x+2)+ (4x^2+2x)(3x-2)

    =  (8x^4+2x^3-16x^2-4x)+(12x^3-8x^2+6x^2-4x)

   = 8x^4+14x^3-10x^2-8x

Mar 18th, 2015

Are you studying on the go? Check out our FREE app and post questions on the fly!
Download on the
App Store
...
Mar 18th, 2015
...
Mar 18th, 2015
Dec 10th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer